Application of a non-invasive measurement technique to detect anomalies in frescoes at the US Capitol. Issue 1 (1st April 2022) - Vignola, A; Corvaro, F; Vignola, J; Turo, D; Marchetti, B; Vitali, M
Abstract: Delamination is one of the most common issue that can affect frescoes and wall painting in general. Non-destructive techniques (NDT) are considered an effective analysis method for frescoes conservation status detection. The objective of this work was to determine the structural integrity of plaster in the United States Capitol Building through structural vibration analysis. The plaster was excited with sound, causing it to vibrate at a miniscule level. The resulting vibrations were measured using a laser vibrometer and then utilized to reveal the location and size of unseen irregularities in the structure. More than 50 individual scans were performed and analyzed using scanning laser Doppler vibrometer (LDV). The analysis identified many anomalies and assessed the status of some areas that were intact. This procedure was performed on each of the frescoes adorning the walls and ceiling of the rooms to discover areas where the painted plaster has lost adherence to the underlying architecture. The frescos were classified into three categories: intact, anomalous, in need of further analysis. A comparison with data recorded in 2004 of the same frescoes has been also performed.